2012
DOI: 10.1590/s0103-21002012000800005
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with adherence to antihypertensive treatment in a primary care unit

Abstract: Objectives: To analyze the adherence of patients to antihypertensive treatment conducted in a Primary Care Unit (PCU), as well as the related factors of low adherence to this therapy. Methods: A quantitative, descriptive exploratory study of hypertensive patients interviewed in a PCU, using the Morisky-Green Test for assessing adherence or nonadherence with antihypertensive treatment. Results: A prevalence of 64% of patients who were nonadherent to antihypertensive therapy was identified, and this was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 7 publications
0
11
0
6
Order By: Relevance
“…Non-medication adherence was associated with working-aged victims who were young, working, and presented with overweight or obesity as found in a study in Brazil (Demoner, de Paula Ramos, & Pereira, 2012). The reasons for drug nonadherence may be due to normalization of blood pressure, side effects of the medications, forgetting to use the medication, cost of medication, fear of mixing alcohol and medication, ignoring the need for continuing the treatment, use of an alternative treatment, fear of intoxication, fear of hypotension, and fear of mixing the medication with other drugs (Andrade, Vilas-Boas, Chagas, & Andrade, 2002).…”
Section: Discussionmentioning
confidence: 57%
“…Non-medication adherence was associated with working-aged victims who were young, working, and presented with overweight or obesity as found in a study in Brazil (Demoner, de Paula Ramos, & Pereira, 2012). The reasons for drug nonadherence may be due to normalization of blood pressure, side effects of the medications, forgetting to use the medication, cost of medication, fear of mixing alcohol and medication, ignoring the need for continuing the treatment, use of an alternative treatment, fear of intoxication, fear of hypotension, and fear of mixing the medication with other drugs (Andrade, Vilas-Boas, Chagas, & Andrade, 2002).…”
Section: Discussionmentioning
confidence: 57%
“…Contudo, é importante ressaltar que os pacientes com resistência orgânica ao tratamento farmacológico podem apresentar alterações na Mapa mesmo utilizando adequadamente os medicamentos, o que sugere cautela na interpretação de seus resultados (RUZICKA; HIREMATH, 2015). No que se refere aos estudos de natureza epidemiológica como este, o TMG e o THS são os medicamentos mais utilizados por serem de fácil aplicação, baixo custo e boa especificidade ((VARLETA; AKEL; ACEVEDO, 2015;DEMONER;RAMOS;PEREIRA, 2012;PUCCI;PEREIRA;VINHOLES, 2012;SANTOS et al, 2011;GONÇALVES, 2010;STRELEC;PIERIN;MION-JR, 2008).…”
Section: Discussionunclassified
“…No Brasil, a maioria dos estudos que abordam esta temática mostra, como resultados mais encontrados, baixa prevalência de adesão ao tratamento anti-hipertensivo (BASTOS-BARBOSA et al, 2012;BUENDIA, 2012;BEM;NEUMANN;MENGUE, 2012;DEMONER;RAMOS;PEREIRA, 2012;GUIRADO;RIBEIRA;HUERGO;BORRAS, 2011;LEÃO E SILVA, et al, 2013;SANTOS et al, 2010).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Other study suggested women tend to be more adherent to therapy than men (Ambaw et al, 2012). Respondents with BMI ≥30 and respondents who did not have other chronic diseases tend to be disobedient compared to those with BMI <30 and have other chronic diseases (Demoner et al, 2012). Another study stated, dietary regulation and smoking activity determine therapy adherence.…”
Section: Introductionmentioning
confidence: 98%